(untitled) (Journal of Pathology of Nepal, 2015)
Background: Thyroid cancer is the commonest endocrine malignancy. Based on recent data, thyroid cancer is the fifth most common cancer in women. To our knowledge the present study is the first of its kind, correlating epidemiological and histomorphological data so as to assess the major cause hypothesis for thyroid cancers, focusing more on papillary carcinoma and its variants, comparing it with each other and with other thyroid carcinomas and also correlating with gender, life style and religion. Materials and methods: This study was conducted in the Department of Pathology, MES Medical College, Perinthalmanna, Kerala, India, from January 2004 to June 2015.Two thousand and fifty thyroidectomy cases were studied. Results: Out of the total 2050 cases, thyroid cancers constituted 295 (14.39%); of which 10.1% (208 cases) were Papillary carcinoma thyroid (PCT) and its variants; 165 cases were seen in females (79.33%) and the incidence in males were only 20.68% (43 cases).The commonest variant encountered was classical papillary carcinoma (113 cases, 54.32%). Conclusion: Our study of papillary thyroid carcino